Wading through black jade in Marianne Moore’s sunken cathedral: The modernist sea poem as a Deleuzian fold - Ambroży, Paulina (Studia Anglica Posnaniensia, 2016)
The study is a close reading of Moore’s poem “The Fish” (1918) through the conceptual lens of Gilles Deleuze’s trope of the fold, as explained in his influential 1988 study of Leibniz, The Fold: Leibniz and the Baroque. The purpose is to explore Moore’s (neo)baroque sensibility and her peculiar penchant for Baroque tropes, images and forms. The Deleuzian concept of the fold, with its rich epistemological implications and broad cultural applicability as the universal trope of crisis, change, unrest and transience, helps to comprehend Moore’s own philosophical and aesthetic concerns. The study, in accord with the interdiscursive character of the contemporary studies of modernism draws from art history, philosophy, theory, literature, and visual arts, to uncover a strong Baroque undercurrent in the poet’s polyphonic imagination. Seen in the light of Deleuze’s fold, Moore’s poem emerges as a quasi-Baroque ruin, a sunken cathedral-cum-graveyard, with a theatrical chiaroscuro lighting and folding and unfolding of sense, which both shelters and entombs the severely wounded modernist soul.